Między literackością a podmiotowością. Nowy wymiar „skażenia” polskiego reportażu (na przykładzie Zapisków na biletach Michała Olszewskiego) - Katarzyna Frukacz (Postscriptum Polonistyczne)
The purpose of this article is to redefine the category of “contamination”, entrenched in the tradition of literary reportage. Due to the process of genre blurring, the original meaning of the term (the one connected with the presence of creational elements in the reporter’s writings) has now been replaced by a more complex definition. The author creates the hypothesis that the “contamination” of contemporary reportage is caused also by the increase of subjective and emotional factors in journalistic narration. To illustrate this assumption, the article provides an analysis of the book Zapiski na biletach. Written by the Polish reporter Michał Olszewski the book serves as an example of genetic changes of the reportage convention.